Eating and Drinking Formula in the Qur’an: A Systematic Study Based on the Integration of Qur’an, Sunnah, Biology and Medicine - Abdillah Kitota (MAQOLAT: Journal of Islamic Studies, 2024)
Non-communicable diseases; related to poor eating habits, present a significant burden on people, as well as economic resources; which in-turn, may affect the effectiveness of saying and doing in the path of Allah (S.W.T). This systematic study was designed to review the guidance of Qur’an on how to avoid this burden; by integrating its verses, ahadith, and signs in the modern Biology and Medicine. Tafsir ibn Kathir and Saheeh International Translation were used to identify the verses that are directly related to this burden. The related ahadith were searched from the six canonical books of ahadith of Ahlu Sunnah Wal-Jama’aa. The related biomedical searches were carried out in PUBMED and MEDLINE databases. Both original and review studies; that were published in the last ten years, were selected. The search terms included food, drink, nutrition, risk factors, and non-communicable diseases. Twenty-four verses, one Hadith, and 23 articles were identified. These verses have revealed the formula on eating and drinking which should be adhered in order to accomplish the mission of our creation, and if not adhered, it may lead to both physical and spiritual effects. This study may have profound contribution on the reduction of this burden; which in turn, may help our capacity building on the work that Allah (S.W.T) has commanded us to do, which is to say and do in His path. It may also rekindle the interest of other researchers to research more on this subject and build up on the formula presented in this study.